#### Question

In the following, determine whether the given values are solutions of the given equation or not:

x^{2} - 3x + 2 = 0, x = 2, x = -1

#### Solution

We have been given that,

x^{2} - 3x + 2 = 0, x = 2, x = -1

Now if x = 2 is a solution of the equation then it should satisfy the equation

So, substituting x = 2 in the equation we get

x^{2} - 3x + 2

= (2)^{2} - 3(2) + 2

= 4 - 6 + 2

= 0

Hence, x = 2 is a solution of the given quadratic equation.

Also, if x = -1 is a solution of the equation then it should satisfy the equation

So, substituting x = -1 in the equation, we get

x^{2} - 3x + 2

= (-1)2 - 3(-1) + 2

= 1 + 3 + 2

= 6

Hence x = -1 is not a solution of the quadratic equation

Therefore, from the above results we find out that x = 2 is a solution and x = -1 is not a solution of the given quadratic equation.